Explaining gender differences in non-fatal suicidal behaviour among adolescents: a population-based study - Kaess, Michael; Parzer, Peter; Haffner, Johann; Steen, Rainer; Roos, Jeanette; Klett, Martin; Brunner, Romuald; Resch, Franz (BMC public health, 2011)
While suicide is the second leading cause of death among young people in most industrial countries, non-fatal suicidal behaviour is also a very important public health concern among adolescents. The aim of this study was to investigate gender differences in prevalence and emotional and behavioural correlates of suicidal behaviour in a representative school-based sample of adolescents.